Anti-arbitration injunctions under English law - Pérez Font, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Under the common law, Courts have the power to restrain a party from commencing or pursuing an abusive arbitration. Given its complex relationship with the kompetenz-kompetenz principle and the principle of minimal curial intervention, English Courts have restricted the use of this power to circumstances which, following the recent decision in the Sodzawiczny case, can be grouped into three basic categories.
Keywords: Anti-arbitration injunctions; English Law